Impact of Weight Loss on Improvement of Insulin Resistance and Reduction of Fatty Hepatic Steatosis in Obese Patients with Type 2 Diabetes - Mohammed, Aya Jasim; Raddam, Qussay Noori; Abdalaziz, Nawar Mohsin (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Obesity and type 2 diabetes mellitus (T2DM) are common metabolic disorders requiring effective non-pharmacological interventions. This study evaluated the effects of a regular dietary intervention program on anthropometric, body composition, and biochemical indicators using a randomized complete block design. Methods: Three groups were included: healthy control, infected (untreated) control, and experimental (dietary program). Anthropometric measures (BMI, BFM, VFA, TBW, protein, minerals, BMR), glycemic indicators (glucose, insulin, HbA1c, HOMA-IR, C-peptide), and liver enzymes (AST, ALT, ALP, GGT) were assessed using SPSS v26. Results: The infected group showed significant elevations in BMI (33.23), BFM (35.70), VFA (171.78 cm²), glucose (176.01 mg/dL), HbA1c (8.52%), and C-peptide. The experimental group demonstrated marked improvement: reduced BMI, a 34% decrease in VFA, a 16.2% decline in glucose (147.45 mg/dL), and an HbA1c reduction to 7.44% — clinically significant, as each 1% reduction in HbA1c lowers cardiovascular risk. C-peptide decreased, reflecting improved β-cell function. Liver enzymes remained within normal ranges, indicating reduced hepatic fat and inflammation. Conclusion: Regular dietary intervention significantly improved anthropometric, glycemic, and metabolic indicators in obese T2DM individuals, though values did not fully normalize. These findings support structured dietary programs as effective interventions for managing obesity-related metabolic dysfunction.